Physiological and anatomical assessments of tetrasporophytes with epiphyte gametophytes of wild and green variant strains of Gracilaria caudata (Gracilariales, Rhodophyta) - Yeh, Mario Celso Machado (2017)
Gracilaria caudata J. Agardh is one of the naturally occurring species in Brazil that produce good quality agar. In Rio do Fogo (RN), Brazil, a green variant was discovered in a G. caudata population of predominantly red (wild phenotype) tetrasporophytes. Epiphytes gametophytes on tetrasporophytes have been observed for both strains. Considering the wild and green variant strains in laboratory control conditions, this study: (i) assessed the impacts of epiphyte gametophytes on tetrasporophytes by evaluating the growth rates, the pigment content, and the photosynthetic potential of the tetrasporophytes; (ii) evaluated the amount of time required for the differentiation of cystocarps in free-living gametophytes and epiphyte gametophytes on tetrasporophytes; (iii) evaluated the number of epiphyte gametophytes produced by tetrasporophyte; and (iv) analyzed anatomical aspects of the intersection between the tetrasporophytes and the tetraspores that germinated on the tetrasporophytes. Samples were cultivated for 12 weeks on laboratory conditions. Control samples had epiphyte gametophytes growing on them, while treatment samples had their epiphyte gametophytes removed weekly. Physiological analyses compared control and treatment samples, while anatomical analysis used the control samples only. Considering the tetrasporophyte growth rates before fertility (2nd week), wild strain showed higher values than green variant; however, after 12 weeks, no differences were found between strains or between samples without epiphyte gametophytes. The wild strain produced tetraspores more frequently than the green variant and showed deficiency in phycoerythrin and allophycocyanin. Green variant treatment samples had higher content of allophycocyanin, phycocyanin and phycoerythrin than the control samples. Chlorophyll a was higher in the wild strain, and treatment samples had lower values in comparison to control samples. Epiphyte gametophytes possibly promoted reduction in pigment content of the tetrasporophytes on both strains. Wild strain samples without epiphyte gametophytes had higher photosynthetic efficiency. Epiphyte gametophytes produced cystocarps one week before free-living gametophytes. The amount of epiphyte gametophytes on tetrasporophytes is not different between strains. Epiphyte gametophytes were visible one week before on the wild strain than in the green variant strain. It was found that tetraspores give rise to epiphyte gametophytes through two distinct germination methods: outside or inside the thallus of the tetrasporophyte. Germination outside the tetrasporophyte thallus was more common, produced visible holdfasts and promoted cortex thickening in the cortical region of the tetrasporophyte. Germination inside the tetrasporophyte thallus did not show evidences of holdfasts nor cortex thickening on the tetrasporophytes. Epiphyte gametophytes holdfasts had adjacent cells to the cortex of the tetrasporophytes when they germinate outside the thallus; however, when germination occurred inside the thallus, the connection interface was closer to the medulla of the tetrasporophyte. Epiphyte gametophytes might represent a new life strategy that promotes sexual variability in a population mostly composed of tetrasporophytes. For cultivation purposes, wild tetrasporophytes with epiphyte gametophytes yielded more mass than the variant tetrasporophytes, being the best option for production. However, the green variant without epiphyte gametophytes produced more phycobiliproteins, making it a better option to harvest those substances